THE EFFECT OF STUDENTS’ PERCEPTION ON LEARNING MEDIA IN A FLIPPED CLASSROOM ON THE STUDENTS’ LEARNING MOTIVATION AT RIAU UNIVERSITY - Nares, Fathiya Inayah Az Zahra; Winarto, Winarto (Universitas Gadjah Mada, 2026)
Background: To address limitations of traditional lectures, the flipped classroom model introduces students to basic material before class, thereby increasing students’ mastery of basic material and reducing the limitations in medical education. One important factor in learning basic medical sciences, such as histology, is learning motivation. The learning media used in a flipped classroom can shape students' perceptions, which may, in turn, influence learning motivation.Aims: This study aims to determine the relationship between student perceptions of learning media in a flipped classroom and their motivation to learn histology at the Faculty of Medicine, Riau University. Methods: This is a quantitative correlational design using questionnaires administered to 118 first-year medical students in the 2024/2025 academic year following the flipped classroom. Students first engaged in independent study by watching instructional videos prepared by the researcher. Six days later, they participated in in-class histology learning activities, including question-and-answer sessions, discussions, and picture quizzes related to the studied content. After those stages of the flipped classroom, students filled out the questionnaire. Thirteen participants were excluded, resulting in a final sample of 105 students. Results: Student perceptions of the learning media (instructional videos) were categorized as good, while their motivation to learn histology in the flipped classroom was high. A Chi-Square test (p = 0.002) indicated a relationship between student perceptions of the learning media and their motivation to learn histology (p < 0.05).